Palladium Catalyzed Electrophilic C2‐Arylation of Azoles by Aryltriazenes in Ionic Liquid Promoted by Acidic Ionic Liquid. Issue 39 (20th October 2020) - Sutar, Suraj M.; Savanur, Hemantkumar M.; Patil, Chidanand; Prabhala, Pavankumar; Aridoss, Gopalakrishnan; Kalkhambkar, Rajesh G.
Abstract: A green C−H bond activation of azole based bio‐pertinent substrates such as benzoxazole, benzothiazole, benzimidazole are accomplished using readily prepared 1‐aryltriazenes as arylating agent. Under an optimized condition employing Pd(OAc)2 and CuI in either hydrophilic [Bmim][BF4 ] or hydrophobic [Bmim][PF6 ] IL medium with [BMIM(SO3 H)][OTf] as a promoter, these arylation reactions proceeded smoothly to afford 2‐aryl substituted azoles in acceptable to better yields besides noticeable functional group tolerance. The prospective for recovery and re‐use of ionic liquid solvent is demonstrated. Abstract : Biologically important aromatic compounds such as benzoxazole, benzothiazole, benzimidazole derivatives were synthesized using 1‐aryltriazenes as a coupling source at C‐2 position in azole rings using ionic liquid as solvent and acid promoter. A green approach is used over traditional methodology to synthesize these compounds in better yields. The recycling and re‐usability of ionic liquid is advantageous in obtaining the greater yields of products.